Modification Of Ropita (Round Spin Table) Education Model As An Effort To Improve Behavior In Maintaining Dental Health In Students At Sdn Sendangmulyo 01, Semarang - Dwi Septiarini (Syntax Corporation Indonesia, 2023)
Background: Dental caries is a multifactorial disease that demineralises dental hard tissues. One of the factors that cause caries is dental hygiene behaviour. The proportion of dental caries in students at SDN 01 Sendangmulyo, Semarang was 80% and the average debris index score was 2,2 with a poor category. Efforts to overcome this problem through modification of the ROPITA (Round Spin Table) education model provide education through game methods so that the learning process is fun and interesting. Objective: To produce a modification of the ROPITA (Round Spin Table) educational model that is feasible and effective in its application as an effort to improve behaviour in maintaining dental health in students at SDN Sendangmulyo 01, Semarang. Methods: Research and Development with true experiment research design (pretest-postest with control group design). The sample totalled 60 respondents including 30 intervention group respondents and 30 control group respondents. Model test data using paired t-test and independent t-test. Results: Expert validation test of the modified ROPITA (Round Spin Table) educational model obtained interclass correllation coefficient with a p-value of 0,001. The results of the independent t-test data effectiveness test of knowledge, attitudes, actions and debris index score obtained a p-value of 0,000 <0,05. Conclusion: Modification of the ROPITA (Round Spin Table) educational model is feasible and its application is effective as an effort to improve behaviour in maintaining dental health in students at SDN 01 Sendangmulyo, Semarang compared to the control group